Submodule power losses balancing algorithms for the modular multilevel converter - Picas, R.; Pou, J.; Zaragoza, J.; Watson, Alan James; Konstantinou, G.; Ceballos, S.; Clare, Jon C. (2016)
Tolerance and component aging can cause signif¬icant differences in the capacitance values of the submodules (SMs) in a modular multilevel converter (MMC). Depending on the modulation technique, capacitance mismatches may produce uneven switching transitions of the SMs, hence imbalances in the power losses that can lead to reliability problems. In this paper, a new algorithm that helps to achieve evenly distributed switching and conduction losses within the converter SMs is presented. The proposed algorithm is based on a modification of the common voltage balancing algorithms, balancing a weighted function of voltage and losses. Even distribution of power losses is achieved at the cost of slightly increasing the capacitor voltage ripples. The effectiveness of the strategy has been demonstrated by simulation results of a high-power grid-connected MMC.